TIC as tools for evaluating curricular content for Higher Technical and Technological Institutes - Rodríguez Wong, Cristian Alberto; Proaño Cobos, Marcelo Ludgardo; Albán Guijarro, María José; Segarra Mendoza, Rosa Esther (Revista Minerva, 2022)
Assessment is often seen as a product, combined with the grades given to students; however, the concept of assessment refers to a continuous process that is essential in teaching and learning. Throughout history, different techniques and strategies have been developed based on the evaluation criteria and the objectives to be achieved today after the pandemic presented by COVID-19, where ICTs have been an essential tool for educational institutions. Despite the prevailing climate of mistrust created by the use of ICT tools, higher institutes, especially in the career of Technology in Assembly and Maintenance of Computer Equipment, where they have been forced to use it as a method of teaching and evaluating the contents. curricula in response to the needs of the educational community. Therefore, this study was carried out with descriptive documentary methods of applied field and as an instrument the survey technique was used, having as a population 22 teachers belonging to the Juan Bautista Aguirre Higher Technological Institute, this was carried out with the purpose of knowing the thinking of teachers on the use of ICT to assess curricular content. Finally, a proposal is proposed based on the ICT tools that teachers who teach in the TEMEC career can use for the evaluations of the curricular units, aligning themselves with the functional criteria of formative and summative evaluation.
Keywords: TIC; Evaluation; Curriculum Content; Institute; Covid-19